Pharmacokinetics of Amikacin in Critical Care Patients on Extracorporeal Device. Issue 5 (September 2018) - Ruiz-Ramos, Jesus; Gimeno, Ricardo; Pérez, Francisca; Ramirez, Paula; Villarreal, Esther; Gordon, Monica; Vicent, Carlos; Remedios Marqués, María; Castellanos-Ortega, Álvaro
Abstract : In this study, we evaluate the effect of extracorporeal membrane oxygenation (ECMO) and ventricular assist devices (Levitronix) on the pharmacokinetic of amikacin in critically ill patients. Twelve patients with ECMO and three with Levitronix devices who started treatment with amikacin were included. Amikacin pre (Cmax) and post (Cmin) dose serum concentrations were measured during the first 72–96 hours of treatment initiation. Pharmacokinetic parameters were performed by Bayesian adjustment. The median initial dose was 1, 000 mg (range: 600–1, 400 mg). Mean plasma concentrations were Cmax 58.6 mg/L (17.0 mg/L); Cmin 9.58 mg/L (7.8 mg/L). Patients with an ECMO device had a higher volume of distribution (0.346 [0.033] vs. 0.288 [0.110] L/kg) and a lower plasma clearance (1.58 [0.21] vs . 3.73 [1.03] L/h) than the control group. This phenomenon was also observed in those patients with simultaneous use of ECMO and hemodilafiltration. For patients with Levitronix system, no significant alterations in the volume of distribution were observed, although a lower plasma clearance was noticed. Placement of ECMO devices alters the pharmacokinetic parameters of amikacin in the critically ill patients and should be considered when selecting the initial dose.